PENGARUH MEDIA BERBASIS WEB (WORDWALL) TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA ISLAM - Anna Maryam; Ahdar; Hamsa (LPPM STAI Muhammadiyah Probolinggo, 2025)
This paper aims to examine whether web-based media (wordwall) has a significant or insignificant effect on the learning outcomes of Islamic Religious Education of grade 3 students at SDIT Bina Insan Parepare. This study uses a quantitative research type. The population of this study was 73 students. The research sample used was 42 samples. Data collection techniques used observation, questionnaires, and documentation. The data analysis techniques used were descriptive statistical analysis techniques and inferential statistical analysis techniques. The results of the study concluded that (1) The use of web-based media (wordwall) on grade 3 students at SDIT Bina Insan Parepare was 87.7% of the established criteria and was included in the Good category. (2) The level of learning outcomes of Islamic Religious Education of grade 3 students at SDIT Bina Insan Parepare was 85% of the established criteria and was included in the High category. (3) There is a significant influence between web-based media (wordwall) on the learning outcomes of Islamic Religious Education of grade 3 students at SDIT Bina Insan Parepare. This is based on the t-test. The t-test obtained a Sig. value of 0.003 <0.05 and obtained a t_count value of 3.147> t_table of 2.021 which means that Ho is rejected and H1 is accepted with a contribution of 19.8%. The implications in this study indicate that web-based media (wordwall) has a significant effect on the learning outcomes of Islamic Religious Education of grade 3 students at SDIT Bina Insan Parepare so that it is necessary to maintain and improve the learning process of Islamic Religious Education that is fun for students and utilize technology in the learning process that can improve the quality of Islamic Religious Education.